Effect on high temperature oxidation behavior of vanadium and titanium element in FeCrC coating - Buytoz, Soner (Springer India, 2022)
This study investigates the microstructure and oxidation property of the coating obtained on 42CrMo4 steel by the TIG method. The results demonstrate that the carbide precipitated in the coating is the type of M7C3 with hexagonal structure for the coating of FeCrC powder. However, the (Ti, V) C carbide with tetragonal-irregular shape was precipitated from the coating when the FeTi and FeV powder additives were added into FeCrC. The thermal behavior of the samples was investigated by the DTA/TG method. The peaks of precipitate phases in the S-1 sample were observed at 752 and 784 degrees C as exothermic peaks, and these peaks were seen combined at 780 degrees C in the S-2- S-4 samples containing TiC and VC. It was determined that the energy required for surface oxidation increased with increasing the amount of FeV in the coating layer.
Keywords: High-temperature oxidation; M7C3; MC; TIG coating